2023
DOI: 10.1038/s41598-023-43390-6
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune dysregulation in multisystem inflammatory syndrome in children (MIS-C)

Johana Isaza-Correa,
Laura Ryan,
Lynne Kelly
et al.

Abstract: MIS-C is a systemic inflammation disorder with poorly characterised immunopathological mechanisms. We compared changes in the systemic immune response in children with MIS-C (n = 12, 5–13 years) to healthy controls (n = 14, 5–15 years). Analysis was done in whole blood treated with LPS. Expression of CD11b and Toll-like receptor-4 (TLR4) in neutrophils and monocytes were analysed by flow cytometry. Serum cytokines (IL-1β, IL-2, IL-6, IL-8, IL-10, IL-Ira, TNF-α, TNF-β, IFN-Υ, VEGF, EPO and GM-CSF) and mRNA leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Children with PIMS-TS had a decreased percentage of CD3+ cells, NK cells and Vδ1 compared to controls [ 21 ]. Rybkina et al found similar results, with a suggestion of a potential role for tissue-derived T cells in the treatment of PIMS-TS.…”
Section: Discussionmentioning
confidence: 99%
“…Children with PIMS-TS had a decreased percentage of CD3+ cells, NK cells and Vδ1 compared to controls [ 21 ]. Rybkina et al found similar results, with a suggestion of a potential role for tissue-derived T cells in the treatment of PIMS-TS.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TLR4 and CD11b antigens on the surface of neutrophils and monocytes was evaluated by ow cytometry. Neutrophils were delineated based on SSC-A and CD66b + positivity as previously described [16], and monocytes were de ned based on SSC-A and CD66b negativity and their subsets based on CD14 and CD16 expression: classical (CD14+/CD16-), intermediate (CD14+/CD16+) and nonclassical (CD14dim/CD16+) [17]. A minimum of 10,000 events were collected, and relative expression of TLR4 and CD11b was expressed as mean uorescence intensity (MFI).…”
Section: Antibodies and Flow Cytometrymentioning
confidence: 99%